2015
DOI: 10.1007/s00586-015-4174-9
|View full text |Cite
|
Sign up to set email alerts
|

One-stage posterior spinal shortening by L5 partial spondylectomy for spondyloptosis or L5–S1 high-grade spondylolisthesis management

Abstract: This novel and efficient one-stage shortening technique offers the possibility to manage lumbosacral kyphosis and spinal local malalignment in L5-S1 SPP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…23,59,[65][66][67] Despite this, a similar technique involving a partial L5 vertebrectomy with resection of the S1 dome and posterior L4-S1 and iliac arthrodesis has been associated with a shorter surgical time, less bleeding, and lower risk of nerve injury. 68,69 Regardless of the interbody fusion used, it is common to perform decompression techniques such as laminectomies, microdiskectomies, and/or foraminotomies to relieve radicular pain. 27,28 Concerning the extent of the arthrodesis, fixation to L4 is preferred when reduction is performed.…”
Section: Resultsmentioning
confidence: 99%
“…23,59,[65][66][67] Despite this, a similar technique involving a partial L5 vertebrectomy with resection of the S1 dome and posterior L4-S1 and iliac arthrodesis has been associated with a shorter surgical time, less bleeding, and lower risk of nerve injury. 68,69 Regardless of the interbody fusion used, it is common to perform decompression techniques such as laminectomies, microdiskectomies, and/or foraminotomies to relieve radicular pain. 27,28 Concerning the extent of the arthrodesis, fixation to L4 is preferred when reduction is performed.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, partial vertebrectomy was first described by Reyes-Sanchez et al (9) in 2002 for the treatment of burst fractures and was successfully applied in other spinal diseases (20,21). Later, Obeid et al (22) described a novel spinal shortening technique using a one-stage posterior L5 partial spondylectomy for the management of L5-S1. This seven-case series study showed its safety and efficiency in spondyloptosis reduction.…”
Section: Discussionmentioning
confidence: 99%
“…First, the reduction ends are technically demanded to be curetted until the cancellous bone is well exposed, thus ensuring direct and tight bone-on-bone contact between two ends under axial compression to enhance osteogenesis (25). However, this technical procedure of cancellous bone-on-bone contact instead of vertebral endplates brings an additional risk of subsidence of the vertebral bodies that are overlapped on each other, as indicated by Obeid et al (22) in their management of L5 spondyloptosis using a partial vertebrectomy. Hereby, adequate circumferential fusion with bone grafting of autogenic bone and allogenic bone grafts is strongly suggested as the supplemental procedure to improve spinal fusion (26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…A recent case series of 7 consecutive patients with L5-S1 spondyloptosis of Meyerding IV spondylolisthesis treated by a 1-stage L5 spondylectomy demonstrated at mean 65 months follow-up that slip percentage improved from 115% to 63% postoperatively and that the PT, LL, and thoracic kyphosis also improved. 79…”
Section: Vertebrectomymentioning
confidence: 99%